2000
DOI: 10.1086/315458
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Human Immunodeficiency Virus–Infected Maternal Environment on Development of Infant Interleukin‐12 Production

Abstract: Monocyte-derived cytokine production by cord blood mononuclear cells (CBMC) from infants born to human immunodeficiency virus (HIV)-positive and -negative women was measured to determine whether monocyte dysfunction could contribute to the accelerated HIV disease of pediatric patients. Production of interleukin (IL)-12, but not that of tumor necrosis factor-alpha and IL-10, was reduced, compared with adult peripheral blood mononuclear cells (PBMC). This deficiency was more pronounced in infants of HIV-positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
63
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 44 publications
3
63
4
Order By: Relevance
“…[19][20][21] Consistent with this hypothesis, we and others have shown that providing exogenous recombinant CD154 increases interleukin 12 (IL-12) production by peripheral mononuclear cells (PBMCs) from HIVinfected donors. [22][23][24] In addition, our recent data indicate that levels of IL-12 p70 production correlate with CD154 expression. 16 Importantly, the CD154 dysregulation described in HIV-infected donors can also be modeled in vitro, following engagement of the CD4 receptor by noninfectious viruses having functional envelope glycoproteins or by native HIV gp120 itself prior to T-cell activation, as we and others have previously shown.…”
Section: Introductionmentioning
confidence: 81%
“…[19][20][21] Consistent with this hypothesis, we and others have shown that providing exogenous recombinant CD154 increases interleukin 12 (IL-12) production by peripheral mononuclear cells (PBMCs) from HIVinfected donors. [22][23][24] In addition, our recent data indicate that levels of IL-12 p70 production correlate with CD154 expression. 16 Importantly, the CD154 dysregulation described in HIV-infected donors can also be modeled in vitro, following engagement of the CD4 receptor by noninfectious viruses having functional envelope glycoproteins or by native HIV gp120 itself prior to T-cell activation, as we and others have previously shown.…”
Section: Introductionmentioning
confidence: 81%
“…Decreased production of IL-12 by CBMC stimulated by Staphylococcus aureus Cowan (SAC) has also been described [25,17]. Since monocytes are the main producers of IL-12 in SACstimulated PBMC, these results also point towards defective activation of neonatal monocytes.…”
Section: Neonatal Monocytes and Macrophagesmentioning
confidence: 93%
“…A progressive decrease in the absolute number of pDCs occurs in the first year of life, but adult levels are reached only around 5 years of age [83]. An age-related increase in the capacity of PBMC to synthesize IL-12 in response to LPS or SAC stimulation has also been reported, but levels of production of such cytokine in 12 month-old children remain low [17,25]. A complex picture is emerging from different studies concerning the capacity of APC from young children to stimulate T cells, depending on the functional readout.…”
Section: The Immune Response In Early Childhood Yearsmentioning
confidence: 99%
“…HIV-specific cellular immune responses can be elicited among a proportion of these infants (11). Reduced interleukin-12 and interleukin-2 production in response to Staphylococcus aureus Cowan and phytohemagglutinin (PHA) stimulation suggests immunosuppressive effects of in utero HIV exposure (3,16). An increase in activated (CD4 ϩ HLA-DR ϩ CD38 ϩ ) and memory (CD4 ϩ CD45RA Ϫ RO ϩ ) lymphocytes suggests in utero antigenic stimulation of CD4 ϩ lymphocytes related to HIV products or antigens associated with opportunistic pathogens (16).…”
mentioning
confidence: 99%
“…These naive cells are, compared to memory T cells, deficient in producing gamma interferon (IFN-␥) (5). Furthermore, neonatal T cells respond weakly to antigen-presenting cells, resulting in further decreased IFN-␥ production (3,19,20). This low IFN-␥ production may result in increased susceptibility to intracellular pathogens, including Mycobacterium tuberculosis (15).…”
mentioning
confidence: 99%